Effects of Nonstoichiometry and Cocatalyst Loading on the Photocatalytic Hydrogen Production with (Y1.5Bi0.5)1−xTi2O7−3x and (YBi)1−xTi2O7−3x Pyrochlores. Issue 2 (16th October 2012) - Merka, Oliver; Raisch, Olga; Steinbach, Frank; Bahnemann, Detlef W.; Wark, Michael; Nino, J.
<x xml:space="preserve">Abstract</x> By adjusting the Ti/(Y+Bi) ratios during synthesis, nonstoichiometric pyrochlores of (Y1.5Bi0.5)1−xTi2O7−3x and (YBi)1−xTi2O7−3x were prepared by an aqueous sol–gel method and annealed at different temperatures. The materials were characterized by X‐ray diffraction and UV–vis reflectance spectroscopy. The samples were tested for photocatalytic hydrogen production in the presence of methanol as sacrificial agent after being loaded with nanoparticles of rhodium or platinum acting as cocatalysts. It was found that materials being completely inactive in a stoichiometric composition can be tuned to good photocatalysts by optimizing the Ti/(Y+Bi) ratio. The increase in activity is supposed to derive from an optimization of the TiO6‐octahedral geometry due to the generation of vacancies inside the structure. Increasing the Bi loading shifts the absorption edge into the visible, but unfortunately, an increase of the bismuth content in the structure also leads to stability issues during photocatalysis, which can be suppressed or at least weakened by a higher cocatalyst loading.